Cause analysis and nursing strategy of chemotherapy-induced phlebitis in cancer patients with peripheral intravenous line placement (肿瘤患者经外周静脉化疗致静脉炎原因分析及护理对策) - WANG Xiaoli (王晓莉); ZHANG Yaru (张亚茹); YUAN Yuling (袁玉玲) (Association of Integrative Nursing, 2023)
Objective To analyze the causes of chemotherapy-induced phlebitis in cancer patients with peripheral intravenous line placement, and to provide evidence for developing preventive measures. Methods The clinical data of 24 patients with chemotherapy-induced phlebitis reported to the hospital adverse event reporting system from July 2016 to July 2022 were retrospectively analyzed. Results Among the 24 patients with phlebitis, there were 14 cases of head and neck cancer, 5 cases of lung cancer, 4 cases of esophageal cancer and 1 case of rectal cancer. Grade 2 phlebitis occurred in 14 cases, grade 3 phlebitis in 8 cases and grade 4 phlebitis in 2 cases. The actual occurrence of phlebitis was related to the gender of the patient, the nature of the chemotherapy drugs, the use of high osmotic pressure and stimulant drugs, large infusion volume, repeated drug administration and nursing staff and other factors. Conclusion It is required to evaluate the difficulty intravenous access by standardized assessment tools, establish the management norms of chemotherapy by peripheral intravenous line, strengthen the education of patients and their families, improve the follow-up after discharge, achieve early detection and early treatment, and reduce the occurrence of chemotherapeutic phlebitis. (目的 分析肿瘤患者经外周静脉化疗导致静脉炎的原因, 为制定防范措施提供依据。方法 回顾性分析2016年7月-2022年7月上报医院安全不良事件报告系统的24例经外周静脉化疗致静脉炎患者的临床资料。结果 24例静脉炎患者中, 头颈部肿瘤患者14例, 肺癌患者5例, 食管癌4例, 直肠癌患者1例。发生2级静脉炎14例、3级静脉炎8例、4级静脉炎2例。静脉炎发生的实际情况与患者性别、输入化疗药物的性质、并用高渗透压及刺激性药物、输液量大、反复多次给药及护理人员等多因素有关。结论 采用标准化量表评估静脉穿刺难度, 建立外周静脉化疗管理规范, 加强患者及家属的宣教, 完善出院后随访, 做到早发现早处理, 减少化疗性静脉炎的发生。)